AUTODESK INVENTOR 2023 COOKBOOK a guide to gaining advanced modeling and automation skills for design engineers through actionable recipes - Bordino, Alexander (PACKT PUBLISHING LIMITED, 2022)
With a recipe-based approach, hone and develop the necessary skills you need to perform mechanical, visualization, and simulation tasks using Autodesk Inventor Key Features Create powerful parametric 3D designs, parts, and assemblies Apply effective modeling techniques to increase automation and promote configuration Enable iLogic-powered rapid configurations and apply Finite Element Analysis for model simulation Book Description Autodesk Inventor is an industry-leading, computer-aided design application for 3D mechanical design, simulation, visualization, and documentation. This book will help to bridge the gap between the fundamentals of this software and the more advanced features, workflows, and environments it has to offer. Using cookbook-style recipes, you'll gain a comprehensive understanding and practical experience in creating dynamic 3D parts, assemblies, and complete designs. You'll also explore a variety of topics, including automation and parametric techniques, collaboration tools, creating sheet metal designs, and design accelerators such as frame generators. As you progress, the chapters will guide you through surface modeling tools, advanced assembly, and simplification tools, along with covering iLogic, Finite Element Analysis, and more. By the end of this book, you'll not only be able to use the advanced functionality within Autodesk Inventor but also have the practical experience you need to deploy specific techniques in your own projects and workflows. What you will learn Build upon the fundamentals of parts, assemblies, and drawings Understand how to use advanced modeling tools such as iFeatures, iLogic, and more Develop your experience with parametric design methodologies Explore surface modeling and project management techniques Design efficiently with design accelerators to drive automation Understand and apply Finite Element Analysis Who this book is for This book is for CAD engineers, mechanical/design engineers, and product designers who have a basic understanding and experience of Inventor fundamentals. It aims to guide and coach you past the basics and into the advanced functionality of the software and environments within it.